Estudio de factibilidad para la creación de un centro de acopio para la comercialización de productos reciclables (cartones, plásticos, hierro) a cargo de un Grupo Asociativo de Recicladores de los barrios San Vicente y Coop. Luz de Occidente, sector centro norte de la cuidad de Quito - Romero Bedoya, Lorena Karina (2015)
Once determined the research problem and the limited existence of a technical management in the marketing process recyclable materials by groups of people in an area of the northwestern part of the city of Quito, intends to conduct a feasibility study for creating a collection center for the marketing of recyclable products (cardboard, plastic, iron), by an Associative Group recyclers neighborhoods Saint Vincent and Coop. Light West, North-East of the city of Quito. The development of this work contains the detailed research problems (Chapter 1); background checks and theoretical principles (Chapter 2); A diagnosis of the current situation regarding recyclable products (cardboard, plastic, iron), establishing levels of supply and demand. (Chapter 3); Conduct a technical-administrative-legal study to analyze the location, available resources, internal organization and legal requirements (Chapter 4); Submit an Economic and Financial study to determine this profitability and sustainability in the medium and long term business. (Chapter 5) and summarize the results and findings of the investigation (Chap. 6) The main conclusions must be the people involved are willing to associate with others doing similar activities and have a common Collection Center in Rumipamba parish. It would run with an investment of $ 57,371.00 $ 12,371.00 which corresponds to equity of the project partners and $ 45,000.00 to be funded through the CFN. As indicators of financial assessment jointly determine that the project is viable, and risk analysis and sensitivity, which has a low risk, it is recommended that it be executed.